2021
DOI: 10.1177/15347354211053647
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Telehealth Music Therapy Services in an Integrative Oncology Setting: A Case Series

Abstract: Providing music therapy in a medical setting has necessarily undergone major changes during the COVID-19 world pandemic. Many programs had to discontinue while others were able to transition to a telehealth model. This paper describes the process of conducting telehealth-based music therapy sessions within an integrative oncology setting in a large cancer hospital. Patients provide feedback regarding benefits and challenges of inpatient, outpatient, and group music therapy using a telehealth model. Benefits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
(14 reference statements)
0
13
0
3
Order By: Relevance
“…In response to COVID-19, many MT programs within cancer centers adapted their services for the virtual environment. 9 - 11 …”
Section: Introductionmentioning
confidence: 99%
“…In response to COVID-19, many MT programs within cancer centers adapted their services for the virtual environment. 9 - 11 …”
Section: Introductionmentioning
confidence: 99%
“…1. Estudios enfocados a tratamientos de enfermedades y problemas de salud con causa física, como el dolor crónico y las lesiones medulares (Casellas et al, 2021;Chai et al, 2020;Folsom et al, 2021;Hansen, 2015;Tamplin et al, 2020). 2.…”
Section: Resultsunclassified
“…Este estudio ofrece una revisión de la literatura sobre musicoterapia empleando la teleasistencia para diferentes problemas de salud. Tras el análisis sistemático de los estudios encontrados, se han revisado diez estudios que muestran logros en: mejora del dolor crónico; reducción de la ansiedad y la angustia; control de la respiración y la voz (Chai et al, 2020;Hansen, 2015;Stegemöller et al, 2020;Tamplin et al, 2020); regulación emocional (Hides et al, 2019;Lightstone et al, 2015); mejora del estado de ánimo, relajación y motivación autopercibida (Casellas et al, 2021;Dassa et al, 2020;Martin et al, 2013); disminución de la ansiedad y mayor conexión social (Folsom et al, 2021). En cuatro estudios se han utilizado nuevas tecnologías en la preparación de músicas personalizadas automatizadas (Chai et al, 2020;Martin et al, 2013), usando aplicaciones como Music eScape y comprobado si ayuda a los jóvenes a identificar y gestionar emociones mediante la escucha de música (Hides et al, 2019).…”
Section: Discussionunclassified
“…Participants were engaged in various activities such as song sharing, lyric themes discussion, and music-assisted relaxation techniques following live music. During the pandemic, the participants reported that the music therapy group provided crucial social connection and support ( Folsom et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%